2022
DOI: 10.3390/microorganisms10050973
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxoplasma gondii Infection in Blood Donors from Western Romania

Abstract: Background: Toxoplasma gondii is estimated to infect 33% of blood donors worldwide, and seroprevalence varies widely between countries. We aimed to evaluate, for the first time, the seroprevalence and risk factors associated with T. gondii in blood donors from Western Romania. Methods: Serologic testing to demonstrate the presence of T. gondii antibodies was conducted in 1347 healthy blood donors. Risk factors for T. gondii infection were assessed through an epidemiological questionnaire. Results: The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…The proportion of IgG-positive women increased with age, up to 46.43% in the age group 45–50 years old, and differences in prevalence among age groups were statistically significant. An increase in seroprevalence with an increase in age is also reported in women of reproductive age in Romania [ 27 , 29 ] and in blood donors from Romania [ 30 ]. The relationship between seroprevalence and age is frequently observed and reflects that the risk of toxoplasmosis infection remains throughout life.…”
Section: Discussionmentioning
confidence: 82%
“…The proportion of IgG-positive women increased with age, up to 46.43% in the age group 45–50 years old, and differences in prevalence among age groups were statistically significant. An increase in seroprevalence with an increase in age is also reported in women of reproductive age in Romania [ 27 , 29 ] and in blood donors from Romania [ 30 ]. The relationship between seroprevalence and age is frequently observed and reflects that the risk of toxoplasmosis infection remains throughout life.…”
Section: Discussionmentioning
confidence: 82%
“…A large study performed in 2009 on healthy people from 11 counties from northwestern and central Romania [ 53 ] reported that the seropositivity rate was 59.48% in the general population, while in western Romania a seroprevalence rate of 64.8% was reported in 2015 [ 54 ]. In healthy blood donors—a group that can estimate the true population prevalence of anti- T. gondii IgG antibodies—Lupu et al [ 55 ] reported a seroprevalence of anti- T. gondii IgG of 45.9% in western Romania in 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Rarely, people can become infected by receiving infected blood from an in fected donor. It is significant to note that not everybody who becomes infected with T. gondii will develop symptoms or expand to critical consequences [52].…”
Section: Blood Transfusionmentioning
confidence: 99%